2013
DOI: 10.4238/2013.december.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in MOV10 and CACNB2 are associated with hypertension in a Chinese Han population

Abstract: ABSTRACT. Human hypertension is a complex, multifactorial disease. Multiple variants associated with hypertension have been identified in the large numbers of genome-wide association studies, meta-analysis, and case-control studies. The present study investigated the association between the single nucleotide polymorphisms (SNPs) of five candidate genes and the susceptibility and prognosis of hypertension in a Chinese Han population. A hospital-based case-control study in a Chinese Han population was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
3
16
1
1
Order By: Relevance
“…Although the association analyses in the Chinese Han population [14,15] and other countries [16,17] suggested that the CACNA1A (rs8182538), CACNA1C (rs758116) and the CACNB2 (rs4373814, rs11014166, rs12258967) polymorphisms were associated with blood pressure and hypertension (no reports about CACNA1S polymorphisms), these SNPs were not consistent with our pre-experimental results (200 cases vs 200 controls, unpublished results). Therefore, based on the haplotype analysis results of the Beijing Han (Chinese Han in Beijing (CHB), HapMap) [18], we chose another 17 SNPs in the genes (CACNA1A, CACNA1C, CACNA1S, CACNB2) that encode the proteins of VDCCs to perform genotyping in the Dai population.…”
Section: Choosing Snps and Genotypingcontrasting
confidence: 72%
See 1 more Smart Citation
“…Although the association analyses in the Chinese Han population [14,15] and other countries [16,17] suggested that the CACNA1A (rs8182538), CACNA1C (rs758116) and the CACNB2 (rs4373814, rs11014166, rs12258967) polymorphisms were associated with blood pressure and hypertension (no reports about CACNA1S polymorphisms), these SNPs were not consistent with our pre-experimental results (200 cases vs 200 controls, unpublished results). Therefore, based on the haplotype analysis results of the Beijing Han (Chinese Han in Beijing (CHB), HapMap) [18], we chose another 17 SNPs in the genes (CACNA1A, CACNA1C, CACNA1S, CACNB2) that encode the proteins of VDCCs to perform genotyping in the Dai population.…”
Section: Choosing Snps and Genotypingcontrasting
confidence: 72%
“…Association analyses in China [14], Lithuanian [17] and Europe [16] have reported the association between CACNB2 polymorphisms (rs4373814 in Chinese Han, rs12258967 in Lithuanian and rs18748804 in Europe) and hypertension. In our study, we found three other positive SNPs (rs17539088, G minor , OR Dominant = 0.732 CI95% Dominant = 0.554-0.966, OR Additive = 0.769 CI95% Additive = 0.616-0.960; rs16917217, G minor , OR Dominant = 0.737 CI95% Dominant = 0.558-0.973, OR Additive = 0.776 CI95% Additive = 0.622-0.969; and rs61839222, A minor , OR Dominant = 0.737 CI95% Dominant = 0.558-0.973, OR Additive = 0.776 CI95% Additive = 0.622-0.969), which suggest a decreased risk, in CACNB2 after logistic regression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association analyses in the Chinese Han population [14,15] and other countries [16,17] suggested that the CACNA1A (rs8182538), CACNA1C (rs758116) and the CACNB2 (rs4373814,…”
Section: Choosing Snps and Genotypingmentioning
confidence: 99%
“…Despite these advancements, genetic variation identified so far only explains ~3–6% of the variance for blood pressure, approximately 1 mmHg per allele systolic blood pressure or 0.5 mmHg per allele diastolic blood pressure [ 8 12 ]. Further, the vast majority of GWASs were performed predominantly in Caucasian populations with only a few studies assessing or replicating in other populations even though high blood pressure burden risk is ranked number one in Southeast Asia, Central Asia, North Africa, and Middle East [ 13 40 ]. This suggests the existence of many more undiscovered SNPs/loci or at the very least SNPs unique to other populations that are not of Caucasian ancestry.…”
Section: Outcomes Of Genome-wide Association Studies On Primary Hymentioning
confidence: 99%